The role of metal ions in X-ray-induced photochemistry - Stumpf, Vasili; Gokhberg, Kirill; Cederbaum, Lorenz S. (Nature chemistry, 2016)
Metal centres in biomolecules are recognized as being particularly sensitive to radiation damage by X-ray photons. This results in such molecules being both susceptible to an effective X-ray-induced loss of function and problematic to study using X-ray diffraction methods, with reliable structures of the metal centres difficult to obtain. Despite the abundance of experimental evidence, the mechanistic details of radiation damage at metal centres are unclear. Here, using ab initio calculations, we show that the absorption of X-rays by microsolvated Mg2+ results in a complicated chain of ultrafast electronic relaxation steps that comprise both intra- and intermolecular processes and last for a few hundred femtoseconds. At the end of this cascade the metal reverts to its original charge state, the immediate environment becomes multiply ionized and large concentrations of radicals and slow electrons build up in the metal's vicinity. We conclude that such cascades involving metal ions are essential to our understanding of radiation chemistry and radiation damage in biological environments.
Gesehen am 19.04.2017